2001
DOI: 10.1053/jlts.2001.27870
|View full text |Cite
|
Sign up to set email alerts
|

Temporary portocaval shunt during liver transplantation with vena cava preservation. Results of a prospective randomized study

Abstract: This study aims to determine whether the use of a temporary portocaval shunt (PCS) improves hemodynamic and metabolic evolution during orthotopic liver transplantation (OLT). Preservation of the vena cava during OLT has gained wide acceptance. However, benefits of adding a temporary PCS to the piggyback technique during the anhepatic phase in patients with cirrhosis have not been shown. Eighty patients with cirrhosis were studied prospectively. They were randomly distributed into two groups: patients with a te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
114
0
3

Year Published

2005
2005
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 107 publications
(119 citation statements)
references
References 23 publications
2
114
0
3
Order By: Relevance
“…A direct comparison of the operative times with and without TPCS was available in 3 studies. 9,10,14 There was no difference in 2 studies, 9,14 and 1 study found that the operative time was shorter in patients undergoing TPCS. 10 The intraoperative blood product transfusion requirement was described in 6 articles.…”
Section: Resultsmentioning
confidence: 91%
See 4 more Smart Citations
“…A direct comparison of the operative times with and without TPCS was available in 3 studies. 9,10,14 There was no difference in 2 studies, 9,14 and 1 study found that the operative time was shorter in patients undergoing TPCS. 10 The intraoperative blood product transfusion requirement was described in 6 articles.…”
Section: Resultsmentioning
confidence: 91%
“…10 The intraoperative blood product transfusion requirement was described in 6 articles. 1,3,8,10,13,14 The number of red blood cell units transfused into patients with a TPCS ranged from 1.1 Ϯ 2.3 to 98.4 Ϯ4.3 units. A comparison of patients with a TPCS and patients without one was reported in 3 articles.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations